Just plug the value for x into the first equation and solve:
(y + 2)² = 4 - y
y² + 4y + 4 = 4 - y
y² + 5y = 0
y(y + 5) = 0
So y can either be 0 or -5.
If y is 0, x = 0 + 2 = 2, so this solution is the point (2, 0).
If y is -5, x = -5 + 2 = -3, so this is (-3, -5).
Check the solutions to verify:
(2, 0):
2² = 4 - 0, check
2 = 0 + 2, check
(-3, -5):
(-3)² = 4 - (-5), check
-3 = -5 + 2, check
2006-12-26 17:18:48
·
answer #1
·
answered by Jim Burnell 6
·
0⤊
0⤋
transfer the y's to the left side and they change the signs so it would be x^2+y=4 and x-y=2 and add the y's and they became cancelled and it would be also the same thing for the others x^2+x=4+2 so its x^2+x=6 and think of a number that is squared and added to itself so its 2 and x=2 substitute x into x-y=2 so 2-y=2 so -y=2-2 because when we transfer the numbers or variables we change the signs so -y=0 then y=0 answer is x=2 , y=0
2006-12-26 18:09:12
·
answer #2
·
answered by Andrew T 1
·
0⤊
0⤋
x² = 4 - y- - - - - -Equation 1
x = y + 2- - - - - -Equation 2
- - - - - - -
Insert the x value equation 2 into equation 1
x² = 4 - y
(y + 2)² = 4 - y
y² + 4Y + 4 = 4 - y
y² + 4Y + 4 - 4 = 4 - y - 4
y² + 4y = - y
y² + 4y + y = - y + y
y² + 5y = 0
y(y + 5) = 0
- - - - - - - -
Roots
y = 0
Insert the y value into equation 1
-------
y + 5 = 0
y + 5 - 5 = 0 - 5
y = - 5. .<=..not used
- - - - - - - - - - - - - -
x² = 4 - y
x² = 4 - 0
x² = 4
x² = √4
x = 2
The answer is x = 2
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
Check for equation 1
x² = 4 - y
(2)² = 4 - 0
4 = 4
- - - - - - -
Check for equation 2
x = y + 2
2 = 0 = 2
2 = 2
- - - - - - - -
The solutioin set is { 2, 0 }
- - - - - - - - - - - -s-
2006-12-27 00:14:38
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
0⤋
x=y+2 so replace x in the 1st equation with y+2 like so: (y+2)^2=4-y,
now (y+2)^2 can be rewritten like this: (y+2)(y+2) which when simplified into a trinomial looks like this:y^2+4y+4, so now you can stick that back into the equation and solve for y. Once you solve for y you can go back to the original equations and solve for x.
2006-12-26 20:52:10
·
answer #4
·
answered by superpsychicman 2
·
0⤊
0⤋
Ok Listen boy here comes the answer
x = y + 2 THUS x^2 = (y+2)^2
is that clear ?
if yes i wil;l continue otherwise it is useless to continue
2006-12-26 17:19:33
·
answer #5
·
answered by gjmb1960 7
·
0⤊
0⤋
First off substitute x in the first eqn with the y+2 in the second.
Now expand the polynomial and move over the 4-y giving you:
y^2 + 5y = 0
Factor the quadratic and then solve for y. Now with these two values of y substitute them back into the second eqn, giving you the two values of x.
2006-12-26 17:17:21
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋